Electric-field-induced structural changes in multilayer piezoelectric actuators during electrical and mechanical loading. (15th June 2017) - Esteves, Giovanni; Fancher, Chris M.; Röhrig, Sören; Maier, Günther A.; Jones, Jacob L.; Deluca, Marco
Abstract: The effects of electrical and mechanical loading on the behavior of domains and phases in Multilayer Piezoelectric Actuators (MAs) is studied using in situ high-energy X-ray diffraction (XRD) and macroscopic property measurements. Rietveld refinement is carried out on measured diffraction patterns using a two-phase tetragonal ( P 4 mm ) and rhombohedral ( R 3 m ) model. Applying an electric field promotes the rhombohedral phase, while increasing compressive uniaxial pre-stress prior to electric field application favors the tetragonal phase. The competition between electrical and mechanical energy leads to a maximal difference between electric-field-induced phase fractions at 70 MPa pre-stress. Additionally, the available volume fraction of non-180° domain reorientation that can be accessed during electric field application increases with compressive pre-stress up to 70 MPa. The origin for enhanced strain and polarization with applied pre-stress is attributed to a combination of enhanced non-180° domain reorientation and electric-field-induced phase transitions. The suppression of both the electric-field-induced phase transitions and domain reorientation at high pre-stresses (>70 MPa) is attributed to a large mechanical energy barrier, and alludes to the competition of the electrical and mechanical energy within the MA during applied stimuli. Graphical abstract: Image 1